2012
DOI: 10.1038/jes.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility of pesticides and polychlorinated biphenyls from house dust: in-vitro methods and human exposure assessment

Abstract: Semi-volatile chemicals like pesticides and polychlorinated biphenyls (PCB) tend to accumulate in house dust. This may result in residues of some parts per million (p.p.m.), closely associated with health impairments and diseases like cancer. To explain these associations, we must establish whether a relevant absorption from house dust into human organisms occurs, and most crucially the release of chemicals, that is, their bioaccessibility. Digestive as well as dermal bioaccessibilities were examined using in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 82 publications
2
30
0
Order By: Relevance
“…This result may be easily explained by the higher permethrin concentrations in indoor air than in outdoor air (Table IV) This research also appears to indicate that dermal contact with dust and indirect dust ingestion constitute the main exposure pathways to permethrin. This result is consistent with the study performed by Ertl et al (15) on chemical exposure due to house dust in Germany. Indeed, they found that permethrin exposure was higher by dermal contact, followed by indirect dust ingestion, and, at much lower levels, by inhalation.…”
Section: Exposure and Health Risk Assessmentsupporting
confidence: 94%
See 2 more Smart Citations
“…This result may be easily explained by the higher permethrin concentrations in indoor air than in outdoor air (Table IV) This research also appears to indicate that dermal contact with dust and indirect dust ingestion constitute the main exposure pathways to permethrin. This result is consistent with the study performed by Ertl et al (15) on chemical exposure due to house dust in Germany. Indeed, they found that permethrin exposure was higher by dermal contact, followed by indirect dust ingestion, and, at much lower levels, by inhalation.…”
Section: Exposure and Health Risk Assessmentsupporting
confidence: 94%
“…(29) They were also consistent with values used by other studies for the calculation of dermal exposure. (15,35) Finally, indoor times (Ti j ) were consistent with most estimates in other studies, such as the European EX-POLIS study (41) and the American NHAPS study, (42) which reported estimates of indoor times between 21 and 23.5 hours per day. These results might indicate that concentration data were the most sensitive parameters in exposure calculations.…”
Section: Limitations and Improvements Of The Exposure Assessment Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…soil, fish and dust). Critically, OCPs are structurally very different to the more polar compounds which are representative of modern pesticides (Ertl and Butte, 2012;Guo et al, 2008;Quiros-Alcala et al, 2012) which may make these findings less transferable to more modern formulations. This represents a significant knowledge gap that needs to be addressed.…”
Section: Vegetablesmentioning
confidence: 98%
“…Oral bioaccessibility studies of dusts have investigated a range of organic contaminants such as PCBs, OCPs, PBDEs and phthalate esters respectively (Ertl and Butte, 2012;Kang et al, 2012Kang et al, , 2013Wang et al, 2013d). Wang et al (2013b) performed a risk assessment of OCPs suggesting dust ingestion as a major route to total OCP exposure for children.…”
Section: Dustsmentioning
confidence: 99%